Economic Report of the President : Transmitted to the Congress - United States. President (Washington United States Govenment Press, 1954)
Represents the annual report of the President's Council of Economic Advisers. Appendix B contains historical tables (from 1959 or earlier) on aspects of income (national, personal, and corporate), production, prices, employment, investment, taxes and transfers, and money and finance.
Include Appendix and Map
Keywords: United States -- Economic history -- Economic policy